A Role of Three-Dimensional (3D)-Reconstruction in the Classification of Lung Adenocarcinoma - Maristela L. Onozato; Veronica E. Klepeis; Yukako Yagi; Mari Mino-Kenudson (Analytical Cellular Pathology)
Background: Three-dimensional (3D)-reconstruction from paraffin embedded sections has been considered laborious and time-consuming. However, the high-resolution images of large object areas and different fields of view obtained by 3D-reconstruction make one wonder whether it can add a new insight into lung adenocarcinoma, the most frequent histology type of lung cancer characterized by its morphological heterogeneity.